Updated morphological description and typification of Aphyllorchis striata and a new variety, Acriopsis densiflora var. subpandurata (Epidendroideae, Orchidaceae) from Malaysia - Jabar, Qistina Anis Mad; Ghazalli, Mohd Norfaizal; Esa, Muhamad Ikhwanuddin Mat; Mohamad, Abdul Latiff; Pungga, Runi Sylvester; Jamaluddin, Zainuddin; Yapp, Edevaldo J.; Akeng, Grippin; Go, Rusea; Besi, Edward Entalai (Phytotaxa, 2026)
We report new findings on two orchids from protected forests in Pahang, Peninsular Malaysia: the mycoheterotrophic Aphyllorchis striata and the epiphytic Acriopsis densiflora var. subpandurata, a newly described variety. Recently collected material enables a reassessment of their morphology and resolution of outstanding taxonomic ambiguities. For A. striata, we provide an updated species description, an identification key for Aphyllorchis in Peninsular Malaysia and Thailand, and designate an epitype to address limitations in earlier type material. For A. densiflora var. subpandurata, we describe the new variety based on its distinct few-flowered inflorescence (8-flowered) and subpandurate labellum and designate its holotype.